Cosmic Crystallography: CCP-Index of Thurston Manifold - Toh, Sing Poh (2002)
The universe is assumed to have negative spatial curvature with 3-dimensional hyperbolic Thurston manifold as the fundamental domain. The universal covering space of the universe is tessellated by fundamental domain through holonomy group. Collecting correlated pair method (CCP-method) is implemented to this model to compute CCP-index which indicates the multi-connectedness of the universe.